2015
DOI: 10.1111/bjh.13486
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic model for mantle cell lymphoma in the rituximab era: a nationwide study in Japan

Abstract: SummaryMantle cell lymphoma (MCL) is essentially incurable with conventional chemotherapy. The MCL International Prognostic Index (MIPI) is a validated specific prognostic index, but was derived from patients with advanced-stage disease primarily in the pre-rituximab era. We analysed 501 MCL patients (median age, 67 years; range 22-90) treated with rituximabcontaining chemotherapy, and evaluated the prognostic factors adjusted by the treatment. Five-year overall survival (OS) in the low, intermediate and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…According to other literatures, factors that could predict the prognosis of MCL patients also included the gender, age, B symptoms, spleen involvement, bone marrow involvement, tumor diameter, peripheral white blood cell count, monocyte count, hemoglobin, β2 microglobulin, and albumin level. [27,3138] In this study, we also found that B symptoms, monocyte count, serum macroglobulin level, and albumin level had significant effects on the OS of patients. The B symptoms, in particular, turned out to be an independent prognostic factor associated with the PFS and OS of the patients, which was consistent with literature reports.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…According to other literatures, factors that could predict the prognosis of MCL patients also included the gender, age, B symptoms, spleen involvement, bone marrow involvement, tumor diameter, peripheral white blood cell count, monocyte count, hemoglobin, β2 microglobulin, and albumin level. [27,3138] In this study, we also found that B symptoms, monocyte count, serum macroglobulin level, and albumin level had significant effects on the OS of patients. The B symptoms, in particular, turned out to be an independent prognostic factor associated with the PFS and OS of the patients, which was consistent with literature reports.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, we found that the MIPI in this study did not have a significant risk stratification function, which was similar to the multi-center and retrospective data from 1 Japanese study. [27] As proposed by Hoster et al, [7] the s-MIPI was more appropriate than the MIPI in the general population in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This is a clinical factor that has been shown to be prognostic in HL as well as non-Hodgkin lymphomas. [32][33][34][35][36][37][38] However, the small number of patients and relative heterogeneity of therapy limit conclusions regarding prognostication.…”
Section: Confirm That Cytomorphology Is Compatible With Gzlmentioning
confidence: 99%
“…Thus, the high CR rate of 82.2% in the present study is notable. Recently, retrospective data of a nationwide study of MCL in Japan were reported . In that study, 501 patients with newly diagnosed MCL with a median age of 67 (range 22‐90) years treated with rituximab‐containing therapy between 1992 and 2012 were analyzed.…”
Section: Discussionmentioning
confidence: 99%